Clinical impact of five large‐scale screening projects for chronic hepatitis B in Chinese migrants in the Netherlands. (2nd May 2016) - Coenen, Sandra; van Meer, Suzanne; Vrolijk, Jan M.; Richter, Clemens; van Erpecum, Karel J.; Mostert, Marijke C.; Veldhuijzen, Irene K.; Reijnders, Jurriën G. P.; van Soest, Hanneke; Dirksen, Kees; Drenth, Joost P. H.; Koene, René P. M.; et al.
Abstract: Background & Aims: In low‐endemic countries it is debated whether first‐generation migrants should be screened for chronic hepatitis B infection. We describe the clinical impact of five large‐scale Dutch screening projects for hepatitis B in first‐generation Chinese migrants. Methods: Between 2009 and 2013 five independent outreach screening projects for hepatitis B targeting first‐generation Chinese migrants were conducted in five main Dutch regions. To explore the relevance of our screening we defined clinical impact as the presence of an indication for: (i) antiviral therapy, (ii) strict follow‐up because of high hepatitis B DNA levels and/or (iii) surveillance for hepatocellular carcinoma. Results: In total, 4423 persons participated in the projects of whom 6.0% ( n = 264) were HBsAg positive. One hundred and twenty‐nine newly diagnosed HBsAg‐positive patients were analysed in specialist care. Among these patients prevalence of cirrhosis was 6.9% and antiviral therapy for hepatitis B was started in 32 patients (25%). In patients without a treatment indication, strict follow‐up because of high hepatitis B DNA levels and/or surveillance for hepatocellular carcinoma was considered indicated in 64 patients (50%). Conclusions: In our screening project in first‐generation Chinese migrants, antiviral treatment, strict follow‐up because of high hepatitis B DNA levels and/or surveillance for hepatocellular carcinoma were considered indicated in three of four analysed HBsAg‐positive patients. These data show that detection of hepatitis B in Chinese migrants can have considerable impact on patient care.